On the Scavenging Ability of Scutellarein against the OOH Radical in Water and Lipid-like Environments: A Theoretical Study - Maciej Spiegel; Tiziana Marino; Mario Prejanò; Nino Russo (MDPI AG, 2022)
The antioxidant capability of scutellarein, a flavonoid extracted from different plants of the Scutellaria family, was computationally predicted by considering its reaction with the OOH radical in both lipid-like and water environments. The pKa and equilibrium behavior in the aqueous phase were also calculated. Different reaction mechanisms involving the most populated species were considered. The work was performed by using the density functional level of theory. The individual, total, and fraction-corrected total rate constants were obtained. The results show that scutellarein has scavenging power against the hydroperoxyl radical similar to that of Trolox, which is generally used as a reference antioxidant.